Endoscopic third ventriculostomy on a microneurosurgery simulator. (December 2013) - Jiang, Di; Hovdebo, Jordan; Cabral, Anne; Mora, Vincent; Delorme, Sébastien
Endoscopic third ventriculostomy is a procedure used to treat hydrocephalus by making a perforation in the floor of the third ventricle of the brain under endoscopic guidance. We report on our initial experience in developing an endoscopic third ventriculostomy simulator for neurosurgery residents, including the definition of the simulation content and integration on NeuroTouch, a simulator for microneurosurgery training. The simulator includes exercises in which the trainee is asked to choose the location of the burr hole and the orientation of the trajectory to the foramen of Monro, or is required to find the third ventricle with a neuro-endoscope and perforate its floor. The simulator provides feedback on trainee performance either graphically or using quantitative metrics. The simulator allows easily switching from endoscopic third ventriculostomy mode to microscopic craniotomy mode using a retractable stereoscope based on a single screen and mirrors, detachable plastic heads, and quick-connect tool handles to give more realistic haptic feedback.